Development and validation of a measurement instrument for student assessment of quality physical education in Chinese secondary schools - Ling Qin; Walter King Yan Ho; Selina Khoo (PLoS ONE, 2025)
There is a growing emphasis on developing Quality Physical Education (QPE) programs. However, a research gap exists due to the lack of measurement instruments to assess QPE for students. This study aimed to develop an instrument to assess QPE implementation and its validity and reliability in China. This study comprised three phases. In Phase 1, a conceptual framework for QPE was established using grounded theory based on interviews with 22 PE teachers and 20 students. In Phase 2, using the conceptual framework from Phase 1, we developed an item pool supported by a literature review, expert evaluations, and student interviews. In Phase 3, a cross-sectional study was conducted with secondary school students (705 participants) to analyse the items and assess the instrument’s reliability and validity through exploratory and confirmatory factor analysis, as well as test-retest analysis. The final 45-item instrument, comprising four subscales (student, family, school, and community) across 10 factors, demonstrated strong validity and reliability. Model fit indices met established thresholds (e.g., CFI and TLI ≥ .90, as well as RMSEA ≤ .08). The composite reliability and average variance extracted values for each factor exceeded.7 and.5, respectively, with the test-retest reliability also exceeding.7, indicating high reliability and validity. This study addresses a critical methodological gap in QPE research by developing a culturally contextualized assessment instrument that explicitly identifies and measures students’ perceptions of QPE implementation. This instrument enables systematic monitoring of QPE practices from students’ perspectives, informing evidence-based policymaking and resource allocation. Integrating student, family, school, and community subscales supports holistic interventions to improve the quality of PE.